Understanding Pediatric Cholelithiasis: A Clinical Review - Rogalidou, Maria (Archives of Clinical and Biomedical Research, 2025)
Cholelithiasis is a common gastrointestinal disorder in adults but remains relatively uncommon in children and adolescents. However, advances in diagnostic imaging—particularly ultrasonography—have led to increased detection rates in pediatric populations. While the condition occurs with similar frequency in both sexes during early childhood, a higher prevalence in females is observed after puberty. Beyond hemolytic disorders, the underlying pathophysiology of gallstone and biliary sludge formation in children is not fully understood. Gallstone formation is associated with hemolytic diseases, hepatobiliary disorders, ileal diseases, previous abdominal surgeries, malabsorption syndromes, cystic fibrosis, obesity, certain medications, family history of gallstones, and, in many cases, idiopathic origins. Pediatric cholelithiasis may be asymptomatic or present with non-specific gastrointestinal symptoms. When symptomatic, clinical manifestations are typically related to complications such as cholecystitis, cholangitis, common bile duct obstruction, and pancreatitis, presenting with abdominal pain, fever, jaundice, and vomiting. There is no established indication for pharmacologic treatment in asymptomatic cases; Ursodeoxycholic acid may be beneficial in select patients, but complete gallstone resolution is rare, and recurrence after discontinuation is common. Symptomatic cholelithiasis generally warrants surgical intervention, with laparoscopic cholecystectomy being the preferred approach. Notably, prophylactic laparoscopic cholecystectomy is recommended in asymptomatic patients with sickle cell anemia due to their increased risk of complications. Surgical management may also be considered for other patients with long-standing asymptomatic cholelithiasis. Conclusion: Although pediatric cholelithiasis remains relatively rare, its recognition is increasing. A comprehensive approach—including risk factor assessment, imaging, and individualized treatment—is essential for effective management and prevention of complications.